Tractates Šabbat and 'Eruvin - Guggenheimer, Heinrich W. (Studia Judaica, 2012)
This volume of the Jerusalem Talmud publishes the first two tractates of the Second Order, Šabbat and 'Eruvin. These tractates deal with discussion of all regulations regarding Shabbat, the weekly day of rest, including the activities prohibited on Shabbat. The tractate 'Eruvin covers questions of definition of what is allowed to do on Shabbat. The Second Order is the last one to be published in Heinrich W. Guggenheimer's edition of the Jerusalem Talmud.